2013
DOI: 10.1111/jcmm.12160
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes export proteasomes by way of microparticles: a possible mechanism for generation of extracellular proteasomes

Abstract: The 20S proteasome is almost exclusively localized within cells. High levels of extracellular proteasomes are also found circulating in the blood plasma of patients suffering from a variety of inflammatory, autoimmune and neoplastic diseases. However, the origin of these proteasomes remained enigmatic. Since the proteome of microparticles, small membrane enclosed vesicles released from cells, was shown to contain proteasomal subunits, we studied whether intact proteasomes are actively released into the extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 42 publications
(59 reference statements)
2
45
0
4
Order By: Relevance
“…For example, inflammation attracts antigen-presenting cells that use (immuno)proteasomes for the breakdown of proteins for presentation in the major histocompatibility complex -I, 35 whereas in vitro studies have shown that T cells excrete proteasomes using exosomes and that this excretion is enhanced when T cells are activated. 36 In contrast, antiproteases were least abundant in the dysbiotic VMB groups. A delicate balance between proteases and antiproteases most likely allows for combating infections, whereas at the same time minimizing tissue damage and inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…For example, inflammation attracts antigen-presenting cells that use (immuno)proteasomes for the breakdown of proteins for presentation in the major histocompatibility complex -I, 35 whereas in vitro studies have shown that T cells excrete proteasomes using exosomes and that this excretion is enhanced when T cells are activated. 36 In contrast, antiproteases were least abundant in the dysbiotic VMB groups. A delicate balance between proteases and antiproteases most likely allows for combating infections, whereas at the same time minimizing tissue damage and inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…(C) Cell extracts from PBMCs derived from control subjects and subject 1 (who harbors the c.367C>T [p.Arg123*] nonsense mutation) were prepared with a detergent-free lysis buffer (TSDG) as previously described. 45,46 20 mg of extract was subsequently exposed to 0.2 mM of the Suc-LLVY-AMC substrate (Bachem) and analyzed on 3%-12% gradient gels (native PAGE, Invitrogen) for chymotrypsin-like activity. Size controls consisted of 1 mg of purified spleen-derived 20S and/or 26S complex, as indicated.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…The increased size of the 20S proteasome complex in these cells could be attributed to its association with additional interacting partners, such as PA28, which is constitutively present in immune cells. 45 Two acquisition times, 0.2 ms (above) and 0.8 ms (below), are shown. (D) 10 mg of whole-cell lysate from PBMCs prepared from control subjects and subject 1 with TSDG buffer were incubated in a final 100 mL volume containing 0.2 mM Suc-LLVY-AMC in quadruplicate and in the presence of 2 mM ATP/DTT for various periods of time, as indicated.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…Показано, что в ответ на различные воздействия происходит перераспределение протеасом в клетке [159][160][161]. Более того, при различных стрессовых воздействиях, например, при разного рода повреждениях или заболеваниях, включая различные формы рака, существенно увеличивается число внеклеточных 20S протеасом (в сыворотке крови, спинномозговой жидкости, жидкости бронхоальвеолярного лаважа) [162][163][164][165][166][167][168].…”
Section: способы регуляции убиквитин-независимой протеасомной деградацииunclassified